Space Weather Induces Changes in the Composition of Atmospheric Escape at Mars - K. G. Hanley; D. L. Mitchell; R. Lillis; C. M. Fowler; J. P. McFadden; R. Jolitz; S. Xu; M. Benna; J. Espley; F. Eparvier; S. Curry (Geophysical Research Letters)
Abstract Mars' dayside ionosphere is maintained primarily by ionization from solar ultraviolet photons and subsequent chemical reactions, with small contributions from other mechanisms such as impact ionization and charge exchange. In December 2023, the Mars Atmosphere and Volatile EvolutioN (MAVEN) mission observed the impact of an interplanetary coronal mass ejection (ICME) on Mars' ionosphere, including strongly enhanced fluxes of suprathermal electrons. We show that this enhancement in suprathermal electron fluxes increased ion production from electron impact, so that dayside electron impact ionization rates exceeded photoionization rates during the ICME. This change in ion production mechanisms led to unusually high densities of the minor ions C+ and O++. Space weather events are known to increase ion escape rates, so changes in ion composition during space weather events have important implications for atmospheric evolution. We show that scaling nominal loss rates to account for space weather may underestimate carbon loss from Mars' atmosphere.